Correlation between Red Cell Distribution Width and Coronary Artery Disease Severity in non-diabetic patients of Punjab Institute of Cardiology (PIC) - Taseer, Muneeza; imran, Baseera; Meer, Isma; Lodhi, Hifza Noor; Fazal, Ayesha; Iqbal, Komal (Journal of Fatima Jinnah Medical University, 2024)
Background: Coronary artery disease (CAD) is one of the major causes of morbidity and mortality. The most accurate method of assessing CAD is angiography. Red cell distribution width (RDW) is the quantitative measure of the size variation of circulating erythrocytes. Recently red cell distribution width has emerged as a marker to assess the severity of CAD. The objective of this study is to evaluate the correlation between RDW and CAD severity. RDW is a simple blood test done in routine patients , that’s why it was chosen for correlation. As compared to angiography , which is cost effective and time consuming , so before performing angiography this simple test can be done to measure severity of CAD . Patients and methods: Eighty patients with coronary angiography performed at Punjab Institute of Cardiology (PIC), Lahore were selected.. The CAD severity was calculated by Gensini score. RDW was obtained from automated hematology analyzer. The correlation between RDW and Gensini score was then statistically analyzed by spearman's correlation . This was a cross sectional analytical study conducted at Punjab Institute of Cardiology (PIC), Lahore. Total eighty patients undergoing “elective “coronary angiography were selected (inclusion criteria). Patients with diabetes mellitus, cerebral infarction, hematological diseases, hepatic diseases, and renal diseases were excluded (exclusion criteria). Results: The study population included 57 (71.3%) male and 23 (28.7%) females. The mean age was population was 55.28±11.1 years. Among the 80 patients, 71 (71/80 =?%) were diagnosed with CAD on angiography and out of these, 21 (21/71 = ?%) patients were having one vessel disease, 22 (22/71=?%) were having two vessel disease and 28 (28/71=?%) were having three vessel disease. Conclusion: No significant correlation between RDW and coronary artery disease severity was obtained, sample size could be the main limitation factor.